Neuroimmune Consequences of eIF4E Phosphorylation on Chemotherapy-Induced Peripheral Neuropathy - Agalave, Nilesh M.; Mody, Prapti H.; Szabo-Pardi, Thomas A.; Jeong, Han S.; Burton, Michael D. (Frontiers in Immunology, 2021)
Chemotherapy-induced peripheral neuropathy (CIPN) is a major dose-limiting side effect that occurs in up to 63% of patients and has no known effective treatment. A majority of studies do not effectively assess sex differences in the onset and persistence of CIPN. Here we investigated the onset of CIPN, a point of therapeutic intervention where we may limit, or even prevent the development of CIPN. We hypothesized that cap-dependent translation mechanisms are important in early CIPN development and the bi-directional crosstalk between immune cells and nociceptors plays a complementary role to CIPN establishment and sex differences observed. In this study, we used wild type and eIF4E-mutant mice of both sexes to investigate the role of eIF4E cap-dependent translation and the contribution of various immune cells and nociceptors in the periphery and glia in the spinal cord during paclitaxel-induced peripheral neuropathy. We found that systemically administered paclitaxel induces pain-like behaviors in both sexes, increases helper T-lymphocytes, downregulates cytotoxic T-lymphocytes, and increases mitochondrial dysfunction in dorsal root ganglia neurons; all of which is eIF4E- dependent in both sexes. We identified a robust paclitaxel-induced, eIF4E-dependent increase in spinal astrocyte immunoreactivity in males, but not females. Taken together, our data reveals that cap-dependent translation may be a key central pathway that would presents relevant therapeutic targets during the early phase of CIPN. By targeting the eIF4E complex, we may reduce or reverse the negative effects associated with chemotherapeutic treatments.